2016
DOI: 10.1590/s1519-99402016000200018
|View full text |Cite
|
Sign up to set email alerts
|

Biometria testicular de ovinos Pantaneiros alimentados com níveis crescentes de glicerina bruta na dieta

Abstract: RESUMO Objetivou-se avaliar o efeito da inclusão de níveis de glicerina bruta na alimentação de cordeiros nas características biométricas e histológicas testiculares. Foram utilizados 24 cordeiros não castrados, confinados com 93,79 ± 5,73 dias de idade e peso corporal de 20,22±2,84kg. Os tratamentos testados foram: 0; 2,5; 5,0 e 7,5% de inclusão de glicerina bruta na matéria seca da dieta em substituição ao milho. Os animais foram abatidos usando a condição corporal como critério em escore de 2,5 a 3,5, em um… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
2
0
2
Order By: Relevance
“…In the present study the observed measurements were lower in both Santa Ines and crossbred. This fact may be explained due to the fact that age and weight of the animals were lower than those studied by the authors, and because the scrotum-testicular biometry has a positive correlation with age and body weight of the animals (Silva et al 2000, Dias et al 2003, Boligon et al 2007, Yokoo et al 2007, Santos et al 2016. Moreira et al (2001) studying sheep Santa Ines submitted to scrotal insulation found that changes in the scrotum--testicular biometry are significant from eight days after the insulation end and the scrotal circumference measures returned to baseline after 50 days of treatment.…”
Section: Resultsmentioning
confidence: 88%
“…In the present study the observed measurements were lower in both Santa Ines and crossbred. This fact may be explained due to the fact that age and weight of the animals were lower than those studied by the authors, and because the scrotum-testicular biometry has a positive correlation with age and body weight of the animals (Silva et al 2000, Dias et al 2003, Boligon et al 2007, Yokoo et al 2007, Santos et al 2016. Moreira et al (2001) studying sheep Santa Ines submitted to scrotal insulation found that changes in the scrotum--testicular biometry are significant from eight days after the insulation end and the scrotal circumference measures returned to baseline after 50 days of treatment.…”
Section: Resultsmentioning
confidence: 88%
“…We did not measure scrotal circumference in the present study. However, a strong correlation exists between the weight of testicles/scrotal sac and scrotal circumference (0.60; Santos et al, 2016a). Thus, animals with heavier testicles would likely have larger scrotal circumference.…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, não observamos efeito (P>0,05) da inclusão da glicerina bruta sobre o diâmetro ou altura do epitélio dos túbulos seminíferos do testículo de bovinos. Resultado similar foi relatado por Santos et al (2016) que reportaram ausência de efeito da glicerina bruta sobre diâmetro ou altura do epitélio dos túbulos seminíferos no testículo de ovinos O glicerol é conhecido pelo seu efeito esclerosante (formação de tecido cicatricial conjuntivo no parênquima tissular) quando aplicado diretamente nos testículos de mamíferos (Lopes e Silva, 2014). Aqui os animais consumiram o máximo de 1 kg de glicerina bruta e 440 g de glicerol (considerando teor de 44% de glicerol na glicerina).…”
Section: Discussionunclassified
“…O uso de glicerina bruta até 24% da matéria seca da dieta parece não provocar lesões histopatológicas no sistema nervoso central, rúmen, fígado, rins e intestinos de novilhos (Leão et al, 2012). Em relação ao sistema reprodutivo, a inclusão de até 7,5 % de glicerina bruta na dieta de machos ovinos parece segura, por não provocar lesões histopatológicas nos testículos de ovinos (Santos et al, 2016). No entanto, estudos avaliando a morfologia e patologia testicular de bovinos alimentados com níveis mais elevados de glicerina bruta são escassos na literatura.…”
Section: Introductionunclassified